'We have to be professional' - Swedish preschool teachers' conceptualisation of digital media - Patrik Hernwall (Universitetsforlaget, 2016)
This paper describes how a group of preschool teachers participating in a design workshop sketched ideas for how ICT (information and communication technology) can be developed in relation to preschool practice. The design process, which was modelled on creative research methods and future workshops, is presented in detail. The main findings, based on a data-driven analysis of verbal and written statements and design sketches, show that ICT is mainly conceptualised as either a possibility in the support of specific competences (such as language development) or a threat to, for example, the notion of real communication and also to well-established conceptualisations of preschool practice.